Water-oxygen-corrosion-resistant SiCf / SiC composite material containing multiple layers of matrixes
By using CVI, SI and PIP processes in SiCf/SiC composites to prepare multi-layer matrix structures, the problem of oxidation and degradation of SiCf/SiC composites in high-temperature water-oxygen corrosion environments is solved, and its resistance to water-oxygen corrosion and strength is significantly improved.
Patent Information
- Application Number
- CN202411404066.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-10-09
AI Technical Summary
SiCf/SiC composites are prone to oxidation and degradation in high-temperature water-oxygen corrosion environments, which limits their application in the field of aero engines.
Chemical vapor deposition (CVI) combined with slurry impregnation (SI) and pioneer impregnation and cracking (PIP) processes were used to prepare high-entropy rare earth silicate modified SiCf/SiC composite materials with multi-layer matrix structure. The substrate of the composite material is the CVI SiC layer, the RE-Si-O layer, the PIP SiC layer, the (4RE0.25)2Si2O7 layer and the CVI SiC layer.
The water-oxygen corrosion resistance of SiCf/SiC composites was significantly improved. After corrosion in a water-oxygen environment of 1400°C, 50vol.%H2O+50vol.%O2 for 50 to 200 hours, the weight loss rate of the modified composites was only 0.11 to 0.5%, and the strength retention rate exceeded 93%.
Smart Images

Figure CN119707515A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of preparation and application of composite material matrix, and relates to a SiC matrix containing a multilayer matrix that is resistant to water and oxygen corrosion. f / SiC composite material, specifically a multi-layer matrix SiC resistant to water and oxygen corrosion f / SiC-(4RE 0.25 )2Si2O7-(4RE 0.25 )2SiO5 composite material preparation method and application. Background Art
[0002] SiC f / SiC composite materials have the advantages of high temperature resistance, oxidation resistance, corrosion resistance, high specific strength, and high specific modulus, and are important candidate materials for the hot end components of aircraft engines. The harsh environment of high temperature and water-oxygen corrosion coupling in aircraft engines makes SiC f / SiC composite materials are easily oxidized and corroded, which limits their application in the field of aircraft engines. Therefore, it is urgent to improve the f / SiC composite materials' water and oxygen corrosion resistance.
[0003] Rare earth silicate materials usually have high melting points, good high temperature stability and high temperature mechanical properties, low oxygen permeability constants and similar properties to SiC. f / SiC has good chemical compatibility and other advantages. If it can be introduced into SiC f / SiC composite material matrix, so that the matrix itself has good water and oxygen corrosion resistance, can improve the composite material's water and oxygen corrosion resistance.
[0004] Rare earth silicate materials are divided into rare earth disilicates (RE2Si2O7) and rare earth monosilicates (RE2SiO5). RE2Si2O7 has a lower CTE and higher thermal conductivity. Among the various crystal structures of RE2Si2O7, only β-RE2Si2O7 and γ-RE2Si2O7 have CTEs that match SiC, while γ-RE2Si2O7 is an impurity stable phase. RE2SiO5 has higher resistance to water vapor corrosion and higher strength. In the crystal structure of RE2SiO5, the CTE of X2-RE2Si2O7 with space group I2 / a is closer to SiC than that of X1-RE2Si2O7 with space group P21 / c. High entropy rare earth silicates with the same crystal structure have better high temperature stability and high temperature oxidation resistance than rare earth silicates of a single rare earth element. In summary, the β-phase high entropy rare earth disilicate (abbreviated as (4RE 0.25 )2Si2O7) and X2 phase high entropy rare earth monosilicate (abbreviated as (4RE 0.25 )2SiO5)The introduction of a mixture of the two into the SiC matrix can maximize the advantages of silicate materials.
[0005] The patent "A SiBCN-RE2Si2O7 synergistically modified silicon carbide ceramic matrix composite material and its preparation method [P] CN116891384A." obtains a ceramic matrix composite material in which RE2Si2O7 surrounds SiBCN by repeated alternating impregnation-cracking. The above technical solution is characterized in that: on the one hand, the RE2Si2O7 distributed discontinuously in the matrix cannot form a good water-oxygen barrier layer, and oxygen and water vapor will enter the interior of the composite material along the defects to corrode SiBCN; on the other hand, during the high-temperature water-oxygen corrosion process, water vapor will consume Si in the rare earth disilicate to generate rare earth monosilicate with a higher thermal expansion coefficient (CTE), so that thermal stress continues to accumulate and lead to the formation of new cracks, providing a new fast channel for the corrosive atmosphere. In addition, the above preparation process requires multiple alternating impregnation and cracking, and the process is cumbersome.
[0006] The patent "A ceramic-based composite material modified by a multiphase oxide ceramic and its preparation method [P] CN117923928A." uses a slurry impregnation method combined with a glass melt infiltration method to prepare a ceramic-based composite material in which high-entropy rare earth disilicate is dispersed in the matrix. The above technical solution is characterized in that: the content of each phase is 60-80wt.% of silicon carbide, 10-30wt.% of high-entropy rare earth disilicate, 1-10wt.% of mullite, and 5-15wt.% of silicon dioxide according to the mass percentage; on the one hand, the high-entropy rare earth disilicate dispersed in the matrix cannot form a continuous water-oxygen barrier layer, and oxygen and water vapor will enter the interior of the composite material along the defects to corrode the matrix, generating rare earth monosilicate and SiO2 with a high CTE, so that thermal stress continues to accumulate and lead to the formation of new cracks, providing a new fast channel for the corrosive atmosphere; on the other hand, SiO2 in the matrix will react with water vapor to generate gaseous volatile substances, accelerating the corrosion of the composite material. In addition, the melt infiltration temperature involved in this method is 1300-1550°C. If domestic third-generation SiC fiber (such as Cansas 3303SiC fiber) is used as reinforcement, such a high melt infiltration temperature will cause severe thermal damage to the fiber and significantly reduce the mechanical properties of the composite material.
[0007] In view of this, the present invention proposes to select (4RE 0.25 )2Si2O7 and (4RE 0.25 )2SiO5 mixture (abbreviated as RE-Si-O) was used to modify the matrix, and high entropy rare earth silicates were introduced into SiC by chemical vapor deposition (CVI) combined with slurry impregnation (SI) and precursor impregnation pyrolysis (PIP) processes. f / SiC composite materials, the combined process method has low preparation temperature, will not damage the fiber, the process flow is simple and controllable, and the raw material cost is low. At the same time, by using the intrinsic modulus / strength difference of the matrix prepared by different processes, the introduction order, distribution and content of the matrix prepared by different processes are reasonably designed, which is expected to synergistically optimize the SiC f / SiC composite materials have strong toughness and water-oxygen corrosion resistance. Summary of the invention
[0008] Technical issues to be solved
[0009] In order to avoid the shortcomings of the prior art, the present invention proposes a SiC containing multi-layer matrix resistant to water and oxygen corrosion f / SiC composite materials, solve SiC f / SiC composite materials are prone to oxidative degradation in high temperature water-oxygen corrosion environments.
[0010] The present invention prepares a high-entropy rare earth silicate-modified SiC with a multilayer matrix structure by combining CVI with SI and PIP processes. f / SiC composite material. It is characterized in that the matrix of the composite material is composed of (1) a CVI SiC layer with a volume fraction of 21.6 to 32 vol.%, (2) a RE-Si-O layer with a volume fraction of 1.7 to 2.6 vol.%, (3) a PIP SiC layer with a volume fraction of 13.2 to 18.6 vol.%, (4) a (4RE 0.25 )2Si2O7 layer, (5) 1.2~3.9vol.% CVI SiC layer.
[0011] Technical Solution
[0012] A SiC containing multi-layer matrix resistant to water and oxygen corrosion f / SiC composite material, characterized in that: the composite material is SiC f / SiC-(4RE 0.25 )2Si2O7-(4R 0.25 )2SiO5; the multilayer substrate is CVISiC layer, RE-Si-O layer, PIP SiC layer, (4RE 0.25 )2Si2O7 layer and CVI SiC layer.
[0013] The volume fractions of the moduli of each layer are: 21.6-32 vol.% CVI SiC layer, 1.7-2.6 vol.% RE-Si-O layer, 13.2-18.6 vol.% PIP SiC layer, 2.3-3.5 vol.% (4RE 0.25)2Si2O7 layer and 1.2~3.9vol.% CVI SiC layer.
[0014] A SiC containing multilayer matrix resistant to water and oxygen corrosion f / SiC composite material, characterized by the following steps:
[0015] Step 1: Preparation of porous SiC f / SiC composite material: The BN interface phase with a thickness of 150-200 nm is deposited on the two-dimensional SiC fiber preform by the CVI process, and then the SiC matrix is deposited to a semi-densified state by the CVI process to obtain a porous SiC f / SiC composite material; the porous SiC f The open porosity of the SiC composite material is controlled to be 20% to 40%;
[0016] Step 2, (4RE 0.25 )2Si2O7 water-based slurry impregnation:
[0017] Vacuum impregnation: Porous SiC f The SiC composite material was placed in a glass drying dish and vacuumed to a pressure range of -0.1 to -0.09 MPa. After maintaining for 0.5 to 1 h, the SiC f / SiC composite immersion (4RE 0.25 )2Si2O7 water-based slurry, continue to vacuum for 0.5 to 1h;
[0018] Pressure impregnation: Porous SiC f The / SiC composite material and the slurry are placed in a closed container and pressurized to 0.7-0.9 MPa, maintained for 0.5-1 hour, then taken out and dried;
[0019] Get (4RE 0.25 )2Porous SiC with Si2O7 content of 1.9 to 2.9 vol.% f / SiC CVI -(4RE 0.25 )2Si2O7 composite materials;
[0020] Step 3: Preparation of rare earth mono / disilicate mixed matrix layer: The porous composite material obtained in step 2 is immersed in the organic precursor PCS solution of SiC ceramics. After cross-linking, curing and cracking, PCS and part of the composite material (4RE 0.25 )2Si2O7 reacts to form X2 phase high entropy rare earth monosilicate, referred to as ((4RE 0.25 )2SiO5), forming a 1.7-2.6 vol.% rare earth mono / disilicate mixed matrix layer (abbreviated as RE-Si-O) in the porous composite material;
[0021] Step 4: Prepare PIP SiC matrix layer: Prepare SiC matrix in the porous composite material obtained in step 3 by PIP process, and repeat the PIP process several times until the density of the composite material reaches 2.40-2.68 g / cm 3 ;
[0022] Step 5: Preparation (4RE 0.25 )2Si2O7 matrix layer: The porous composite material obtained in step 4 is immersed in (4RE 0.25 )2Si2O7 water-based slurry, repeat step 2 until 2.3-3.5 vol.% (4RE 0.25 )2Si2O7 matrix layer, making the composite material density reach 2.53~2.87g / cm 3 ;
[0023] Step 6: Prepare CVI SiC matrix layer: Prepare SiC matrix in the composite material obtained in step 5 by CVI process to obtain SiC containing multilayer matrix. f / SiC CVI -(RE-Si-O)-SiC PIP -(4RE 0.25 )2Si2O7-SiC CVI Composite material, referred to as SiC f / SiC-(4RE 0.25 )2Si2O7-(4RE 0.25 )2SiO5 composite materials;
[0024] The SiC substrate has a thickness of 30 to 50 μm.
[0025] The SiC fiber preform is a woven two-dimensional SiC fiber preform.
[0026] The (4RE 0.25 The preparation of 4RE2Si2O7 slurry is as follows: 1. Four RE2O3 and SiO2 are mixed evenly in equal molar ratios and then sintered at 1300-1700°C to obtain β-phase high entropy rare earth double silicate ceramics (abbreviated as (4RE 0.25 )2Si2O7), (4RE 0.25 )2Si2O7 was crushed and milled in a planetary ball mill with ethanol as the ball milling medium and agate ball milling beads for 5 to 15 hours, and then dried to obtain ceramic particles with a particle size of 1 to 10 μm; sodium carboxymethyl cellulose was added to deionized water in 3 to 6 portions, and a magnetic stirrer was used to quickly disperse the sodium carboxymethyl cellulose in the water, and then (4RE 0.25 )2Si2O7 ceramic particles are ball-milled to obtain (4RE0.25 )2Si2O7 water-based slurry; (4RE 0.25 )The mass fraction of 2Si2O7 is +910~30wt.%, the mass fraction of sodium carboxymethyl cellulose is 3~5wt.%, the ball milling time is 8~24h, and the ball milling speed is 100~380r / min.
[0027] The RE2O3 is selected from any four of Sc2O3, Y2O3, Tb2O3, Ho2O3, Er2O3, Tm2O3, Dy2O3, Gd2O3, Yb2O3, and Lu2O3.
[0028] The drying temperature in the pressure impregnation of step 2 is 80° C. to 150° C., and the drying time is 4 to 8 hours.
[0029] In the step 3, the PCS solution, an organic precursor of SiC ceramics, is prepared by mixing polycarbosilane and xylene in a mass ratio of 1:1 to 1:20.
[0030] The cross-linking, curing and cracking process in step 3 is: in an argon atmosphere, the composite material is kept at 200-240° C. for 1-2 hours and at 1300-1400° C. for 2-3 hours.
[0031] The PIP process in step 4 is: in an argon atmosphere, the composite material is kept at 220° C. for 1 to 2 hours, and at 1000 to 1300° C. for 1 to 2 hours.
[0032] A SiC containing multilayer matrix resistant to water and oxygen corrosion f / SiC composite material, characterized in that the density of the composite material is 2.58-2.98 g / cm 3 , the open porosity is 2% to 8%. After being corroded in a water-oxygen environment at 1100 to 1400°C and 50 vol.% H2O + 50 vol.% O2 for 50 to 200 hours, the weight loss rate of the modified composite material is only 0.11 to 0.5%, and the strength retention rate exceeds 93%. SiC f The water-oxygen corrosion resistance of SiC composite materials is greatly improved, making it an ideal material for aircraft engines in high temperature and water-oxygen corrosion coupling environments, which helps to improve the working efficiency of the engine.
[0033] Beneficial Effects
[0034] The present invention proposes a SiC containing multi-layer matrix resistant to water and oxygen corrosion f / SiC composite material is a preparation method of chemical vapor deposition (CVI) combined with slurry impregnation (SI) and precursor impregnation pyrolysis (PIP) process. The SiC prepared by this method f / SiC-(4RE0.25 )2Si2O7-(4RE 0.25 )2SiO5 composite material has the function of resisting water and oxygen corrosion. The matrix of the composite material is distributed in layers, from the inside to the outside, it is (1) CVI SiC layer with a volume fraction of 21.6-32 vol.%, (2) 1.7-2.6 vol.% high entropy rare earth mono / disilicate mixed matrix layer (abbreviated as RE-Si-O layer), (3) 13.2-18.6 vol.% PIP SiC layer, (4) 2.3-3.5 vol.% β-phase high entropy rare earth disilicate (abbreviated as (4RE 0.25 )2Si2O7 layer), (5) 1.2~3.9vol.% CVI SiC layer. In the matrix, the layered high entropy rare earth silicate can effectively block the corrosion of water and oxygen corrosive atmosphere to the interface phase, fiber and PIP SiC matrix of the composite material; the SiC matrix prepared by CVI process has high purity and good crystallinity, and it is uniformly and continuously coated on (4RE 0.25 )2Si2O7 layer, which can not only ensure the mechanical properties of the composite material, but also reduce the water and oxygen corrosion channel. f / SiC-(4RE 0.25 )2Si2O7-(4RE 0.25 )2SiO5 composite material not only has good resistance to high temperature water and oxygen corrosion, but its unique modulus difference layered matrix also gives the composite material good strength and toughness.
[0035] The beneficial effects of the present invention are:
[0036] 1. A multi-layered matrix SiC resistant to water and oxygen corrosion prepared by the present invention f / SiC-(4RE 0.25 )2Si2O7-(4RE 0.25 )2SiO5 composite material adopts a unique matrix structure, which is CVI SiC layer, RE-Si-O layer, PIP SiC layer, (4RE 0.25 )2Si2O7 layer and the outermost CVI SiC layer. The CVI SiC matrix deposited first fills the pores in the fiber bundle, which is beneficial to load transfer and protect the interface phase and fiber; the PIP SiC matrix generated by pyrolysis first fills the pores between the fiber bundles, which is beneficial to improve the densification of the composite material, and at the same time plays a key role in transferring loads and ensuring the mechanical properties of the material; due to SiC fThe pores and defects in the CVI SiC composite material are inevitable, and the oxidizing medium may corrode the interface and fiber of the material through these channels, resulting in performance degradation. However, the RE-Si-O layer between the CVI SiC and PIP SiC layers in the present invention forms a continuous water-oxygen barrier layer, which effectively prevents the corrosion of the fiber and interface by the high-temperature water-oxygen corrosive atmosphere; in addition, the (4RE 0.25 The 2Si2O7 layer not only matches the CTE of SiC, but also has a high thermal conductivity, which helps to reduce the thermal stress inside the material. This layer can also react with water vapor that penetrates into the material to generate (4RE) with a low oxygen permeability constant. 0.25 )2SiO5 protects the PIP SiC layer from corrosion; the outermost CVI SiC layer provides additional protection for the composite material with its high purity, excellent crystallinity and antioxidant properties, which can not only ensure the mechanical properties of the composite material, but also reduce the water and oxygen corrosion channels, effectively improving its environmental performance. f Compared with the SiC / SiC composite material, the SiC f / SiC-(4RE 0.25 )2Si2O7-(4RE 0.25 )2SiO5 composite material has achieved a significant improvement of more than 40% in resistance to high temperature water and oxygen corrosion.
[0037] 2. SiC prepared by the present invention f / SiC-(4RE 0.25 )2Si2O7-(4RE 0.25 )2SiO5 composite material matrix is a layered structure, and there are differences in high and low modulus between different matrix layers. This difference makes it easier for cracks to deflect between matrix layers, prolonging the crack propagation path, effectively absorbing and consuming crack propagation energy, and thus significantly improving the toughness of the material. SiC prepared by combining CVI with PIP process f Compared with / SiC composite materials, the bending strength is increased by more than 10% and the fracture toughness is increased by more than 20%, achieving synergy of strength and toughness.
[0038] 3. The RE-Si-O layer prepared by the present invention is composed of (4RE 0.25 )2Si2O7 and (4RE 0.25 )2SiO5 mixture, of which (4RE 0.25 )2SiO5 is produced by the PIP process (4RE 0.25 )2Si2O7 is obtained by reacting with polycarbosilane. Compared with the reported solid phase reaction and sol-gel method to prepare (4RE 0.25)2SiO5, the method can be used to directly prepare RE-Si-O layer and SiC layer, which has the advantages of simple preparation process and short cycle. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 For SiC f / SiC-(4RE 0.25 )2Si2O7-(4RE 0.25 )2SiO5 composite material preparation process flow chart;
[0040] Figure 2 is the X-ray diffraction pattern of the high entropy rare earth silicate in Example 1;
[0041] Figure 3 The energy scattering spectrum of the high entropy rare earth silicate in Example 1;
[0042] Figure 4 For the SiC in Example 3 f / SiC-(4RE 0.25 )2Si2O7-(4RE 0.25 )X-ray diffraction pattern of 2SiO5 composite material;
[0043] Figure 5 For the SiC in Example 3 f / SiC-(4RE 0.25 )2Si2O7-(4RE 0.25 )2The force-displacement curve of SiO5 composite material;
[0044] Figure 6 For the SiC in Example 4 f / SiC-(4RE 0.25 )2Si2O7-(4RE 0.25 )2SiO5 composite material microstructure;
[0045] Figure 7 For the SiC in Example 4 f / SiC-(4RE 0.25 )2Si2O7-(4RE 0.25 ) Force-displacement curves of 2SiO5 composite materials before and after water-oxygen corrosion; DETAILED DESCRIPTION
[0046] The present invention will now be further described with reference to the embodiments and the accompanying drawings:
[0047] A multi-layered matrix SiC resistant to water and oxygen corrosion f / SiC-(4RE 0.25 )2Si2O7-(4RE 0.25)2SiO5 composite material preparation method and application thereof, the preparation method specifically comprises the following steps:
[0048] Step 1. Preparation of porous SiC f / SiC composite materials:
[0049] The CVI process is used to deposit a BN interface phase with a thickness of 150 to 200 nm on the woven two-dimensional SiC fiber preform, and then the CVI process is used to deposit the SiC matrix to a semi-densified state to obtain a porous SiC with an open porosity controlled at 20% to 40%. f / SiC composite materials;
[0050] Step 2. Preparation of (4RE 0.25 )2Si2O7 particles:
[0051] The four RE2O3 and SiO2 were mixed in equal molar ratios and sintered at 1300-1700℃ to obtain (4RE 0.25 )2Si2O7, (4RE 0.25 )2Si2O7 is crushed and then milled in a planetary ball mill with ethanol as the ball milling medium and agate ball milling beads for 5 to 15 hours, and then dried to obtain ceramic particles with a particle size of 1 to 10 μm;
[0052] The RE2O3 is selected from four of Sc2O3, Y2O3, Tb2O3, Ho2O3, Er2O3, Tm2O3, Dy2O3, Gd2O3, Yb2O3, and Lu2O3;
[0053] Step 3. Preparation of (4RE 0.25 )2Si2O7 slurry:
[0054] Add sodium carboxymethyl cellulose to deionized water in 3 to 6 portions, use a magnetic stirrer to quickly disperse the sodium carboxymethyl cellulose in water, and then add the (4RE 0.25 )2Si2O7 ceramic particles are ball-milled to obtain (4RE 0.25 )2Si2O7 water-based slurry. (4RE 0.25 ) The mass fraction of 2Si2O7 is 10-30wt.%, the mass fraction of sodium carboxymethyl cellulose is 3-5wt.%, the ball milling time is 8-24h, and the ball milling speed is 100-380r / min;
[0055] Step 4.(4RE 0.25 )2Si2O7 slurry impregnation:
[0056] Vacuum impregnation: The porous SiC obtained in step 1 fThe SiC composite material was placed in a glass drying dish and vacuumed until the pressure inside the glass dish was lower than -0.09 MPa. After maintaining for 0.5 to 1 hour, the SiC f The / SiC composite material is immersed in the slurry obtained in step 3, and vacuuming is continued for 0.5 to 1 hour;
[0057] Pressure impregnation: Porous SiC f The / SiC composite material and the slurry are placed in a closed container and pressurized to 0.8MPa, maintained for 0.5 to 1h, then taken out and dried;
[0058] Repeat this step 1 to 4 times until you get (4RE 0.25 )2Porous SiC with Si2O7 content of 1.9 to 2.9 vol.% f / SiC CVI -(4RE 0.25 )2Si2O7 composite materials;
[0059] Step 5. Preparation of rare earth mono / disilicate mixed matrix layer:
[0060] The porous composite material obtained in step 4 is immersed in the organic precursor (PCS) solution of SiC ceramics. After cross-linking, curing and cracking, PCS and part of the composite material (4RE 0.25 )2Si2O7 reacts to generate (4RE 0.25 )2SiO5, forming a 1.7 to 2.6 vol.% RE-Si-O layer in the porous composite material.
[0061] Step 6. Preparation of PIP SiC substrate layer:
[0062] The SiC matrix was prepared in the porous composite material obtained in step 5 by using the PIP process, and the PIP process was repeated 2 to 9 times until the density of the composite material reached 2.40 to 2.68 g / cm 3 .
[0063] Step 7. Preparation of (4RE 0.25 )2Si2O7 matrix layer:
[0064] The porous composite material obtained in step 6 is immersed in the slurry obtained in step 3, and step 4 is repeated until 2.3-3.5 vol.% (4RE 0.25 )2Si2O7 matrix layer, making the composite material density reach 2.53~2.87g / cm 3 ;
[0065] Step 8. Preparation of CVI SiC substrate layer:
[0066] The SiC matrix is prepared in the composite material obtained in step 7 by using the CVI process, and finally a SiC matrix containing a multilayer matrix is obtained. f / SiC CVI -(RE-Si-O)-SiC PIP -(4RE 0.25 )2Si2O7-SiC CVI Composite material (abbreviated as SiC f / SiC-(4RE 0.25 )2Si2O7-(4RE 0.25 )2SiO5 composite material), the density of which is 2.58~2.98g / cm 3 , the open porosity is 2% to 8%.
[0067] In step 4, the drying temperature is greater than 80° C. and the drying time is 4 to 8 hours.
[0068] In the step 5, the organic precursor (PCS) solution of SiC ceramics is prepared by mixing polycarbosilane and xylene in a mass ratio of 1:1 to 1:20;
[0069] In step 5, the cross-linking, curing and cracking processes are as follows: in an argon atmosphere, the composite material is kept at 240° C. for 2 hours and at 1400° C. for 2 hours.
[0070] In step 6, the PIP process is: in an argon atmosphere, the composite material is kept at 220° C. for 1 hour and kept at 1000-1300° C. for 1 hour.
[0071] In the step 8, the thickness of the SiC substrate prepared by the CVI process is 30 to 50 μm.
[0072] The multi-layer matrix composite material resistant to water and oxygen corrosion, high entropy rare earth silicate modified SiC f The water-oxygen corrosion resistance of the SiC / SiC composite material has been greatly improved. For example, after 50 hours of corrosion in a water-oxygen environment at 1400°C and 50 vol.% H2O+50 vol.% O2, the weight loss rate of the modified composite material was only 0.11%, and the strength retention rate exceeded 93%. Specific embodiment:
[0074] Embodiment 1
[0075] Step 1. Preparation of porous SiC f / SiC composite materials:
[0076] The CVI process was used to deposit a BN interface phase with a thickness of 180 nm on the woven two-dimensional SiC fiber preform, and then the CVI process was used to deposit the SiC matrix to a semi-densified state to obtain a porous SiC with an open porosity controlled at 30%.f / SiC composite materials;
[0077] Step 2. Preparation of (4RE 0.25 )2Si2O7 particles:
[0078] Four kinds of RE2O3 and SiO2 were mixed in equal molar ratios and sintered at 1550℃ to obtain (4RE 0.25 )2Si2O7, (4RE 0.25 )2Si2O7 was crushed and then milled in a planetary ball mill with ethanol as the milling medium and agate milling beads for 10 hours, and then dried to obtain ceramic particles with a particle size of 3 μm; the four RE2O3 are Y2O3, Tm2O3, Yb2O3 and Lu2O3;
[0079] Step 3. Preparation of (4RE 0.25 )2Si2O7 slurry:
[0080] Sodium carboxymethyl cellulose was added to deionized water in three portions, and a magnetic stirrer was used to quickly disperse the sodium carboxymethyl cellulose in water. Then, the (4RE prepared in step 2 was added. 0.25 )2Si2O7 ceramic particles are ball-milled to obtain (4RE 0.25 )2Si2O7 water-based slurry. (4RE 0.25 )2Si2O7 has a mass fraction of 25wt.%, a mass fraction of sodium carboxymethyl cellulose of 3wt.%, a ball milling time of 24h, and a ball milling speed of 280r / min;
[0081] Step 4.(4RE 0.25 )2Si2O7 slurry impregnation:
[0082] Vacuum impregnation: The porous SiC obtained in step 1 f The SiC composite material was placed in a glass drying dish and vacuumed until the pressure inside the glass dish was lower than -0.09 MPa. After maintaining for 0.5 h, the SiC f The / SiC composite material is immersed in the slurry obtained in step 3 and vacuum is continued for 0.5h;
[0083] Pressure impregnation: Porous SiC f The SiC / SiC composite material and the slurry were placed in a closed container and pressurized to 0.8 MPa, kept for 1 hour, then taken out and dried in an oven at 100°C for 5 hours;
[0084] Repeat this step 2 times until you get (4RE 0.25 )Porous SiC with 2.0 vol.% Si2O7 content f / SiC CVI -(4RE 0.25)2Si2O7 composite materials;
[0085] Step 5. Preparation of rare earth mono / disilicate mixed matrix layer:
[0086] The porous composite material obtained in step 4 is immersed in the organic precursor (PCS) solution of SiC ceramics. After cross-linking, curing and cracking, PCS and part of the composite material (4RE 0.25 )2Si2O7 reacts to generate (4RE 0.25 )2SiO5, forming a 1.7 vol.% RE-Si-O layer in the porous composite material.
[0087] Step 6. Preparation of PIP SiC substrate layer:
[0088] The SiC matrix was prepared in the porous composite material obtained in step 5 by using the PIP process. The PIP process was repeated 3 times until the density of the composite material reached 2.45 g / cm 3 .
[0089] Step 7. Preparation of (4RE 0.25 )2Si2O7 matrix layer:
[0090] The porous composite material obtained in step 6 was immersed in the slurry obtained in step 3, and step 4 was repeated until 3.2 vol.% (4RE 0.25 )2Si2O7 matrix layer, making the composite material density reach 2.62g / cm 3 ;
[0091] Step 8. Preparation of CVI SiC substrate layer:
[0092] Using the CVI process, a SiC matrix with a thickness of 32.5 μm was prepared in the composite material obtained in step 7, and finally a SiC matrix containing a multilayer matrix was obtained. f / SiC-(4RE 0.25 )2Si2O7-(4RE 0.25 )2SiO5 composite materials.
[0093] The matrix of the modified composite material prepared in this embodiment is composed of a CVI SiC layer with a volume fraction of 25 vol.%, a RE-Si-O layer with a volume fraction of 1.7 vol.%, a PIP SiC layer with a volume fraction of 13.2 vol.%, and a (4RE 0.25 )2Si2O7 layer, 1.6vol.% CVI SiC layer, its density is 2.67g / cm 3 The open porosity is 8%, the bending strength and fracture toughness are 470±25MPa and 28.8±2.5MPa·m1 / 2 The X-ray diffraction pattern and energy spectrum analysis diagram of the high entropy rare earth silicate prepared in this embodiment are as follows: Figure 2 , Figure 3 As shown, it can be seen that β-phase high-entropy rare earth double silicate was successfully prepared.
[0094] Embodiment 2
[0095] Step 1. Preparation of porous SiC f / SiC composite materials:
[0096] The CVI process was used to deposit a BN interface phase with a thickness of 180 nm on the woven two-dimensional SiC fiber preform, and then the CVI process was used to deposit the SiC matrix to a semi-densified state to obtain a porous SiC with an open porosity controlled at 30%. f / SiC composite materials;
[0097] Step 2. Preparation of (4RE 0.25 )2Si2O7 particles:
[0098] Four kinds of RE2O3 and SiO2 were mixed in equal molar ratios and sintered at 1550℃ to obtain (4RE 0.25 )2Si2O7, (4RE 0.25 )2Si2O7 was crushed and then milled in a planetary ball mill with ethanol as the milling medium and agate milling beads for 10 hours, and then dried to obtain ceramic particles with a particle size of 3 μm; the four RE2O3 are Y2O3, Tm2O3, Yb2O3 and Lu2O3;
[0099] Step 3. Preparation of (4RE 0.25 )2Si2O7 slurry:
[0100] Sodium carboxymethyl cellulose was added to deionized water in three portions, and a magnetic stirrer was used to quickly disperse the sodium carboxymethyl cellulose in water. Then, the (4RE prepared in step 2 was added. 0.25 )2Si2O7 ceramic particles are ball-milled to obtain (4RE 0.25 )2Si2O7 water-based slurry. (4RE 0.25 )2Si2O7 has a mass fraction of 15wt.%, a mass fraction of sodium carboxymethyl cellulose of 3wt.%, a ball milling time of 24h, and a ball milling speed of 280r / min;
[0101] Step 4.(4RE 0.25 )2Si2O7 slurry impregnation:
[0102] Vacuum impregnation: The porous SiC obtained in step 1 fThe SiC composite material was placed in a glass drying dish and vacuumed until the pressure inside the glass dish was lower than -0.09 MPa. After maintaining for 0.5 h, the SiC f The / SiC composite material is immersed in the slurry obtained in step 3 and vacuum is continued for 0.5h;
[0103] Pressure impregnation: Porous SiC f The SiC / SiC composite material and the slurry were placed in a closed container and pressurized to 0.8 MPa, kept for 1 hour, then taken out and dried in an oven at 100°C for 5 hours;
[0104] Repeat this step 3 times until you get (4RE 0.25 )Porous SiC with 2.6 vol.% Si2O7 content f / SiC CVI -(4RE 0.25 )2Si2O7 composite materials;
[0105] Step 5. Preparation of rare earth mono / disilicate mixed matrix layer:
[0106] The porous composite material obtained in step 4 is immersed in the organic precursor (PCS) solution of SiC ceramics. After cross-linking, curing and cracking, PCS and part of the composite material (4RE 0.25 )2Si2O7 reacts to generate (4RE 0.25 )2SiO5, forming a 2.4 vol.% RE-Si-O layer in the porous composite material.
[0107] Step 6. Preparation of PIP SiC substrate layer:
[0108] The SiC matrix was prepared in the porous composite material obtained in step 5 by using the PIP process. The PIP process was repeated 4 times until the density of the composite material reached 2.49 g / cm 3 .
[0109] Step 7. Preparation of (4RE 0.25 )2Si2O7 matrix layer:
[0110] The porous composite material obtained in step 6 was immersed in the slurry obtained in step 3, and step 4 was repeated until 3.4 vol.% (4RE 0.25 )2Si2O7 matrix layer, making the composite material density reach 2.67g / cm 3 ;
[0111] Step 8. Preparation of CVI SiC substrate layer:
[0112] Using the CVI process, a SiC matrix with a thickness of 37.3 μm was prepared in the composite material obtained in step 7, and finally a SiC matrix containing a multilayer matrix was obtained. f / SiC-(4RE 0.25 )2Si2O7-(4RE 0.25 )2SiO5 composite materials.
[0113] Compared with Example 1, the volume fraction of the RE-Si-O layer is changed in this embodiment. The matrix of the prepared modified composite material is composed of a CVI SiC layer with a volume fraction of 25 vol.%, a RE-Si-O layer with a volume fraction of 2.4 vol.%, a PIP SiC layer with a volume fraction of 13.2 vol.%, and a (4RE 0.25 )2Si2O7 layer, 1.84vol.% CVI SiC layer, its density is 2.73g / cm 3 The open porosity is 6%, the bending strength and fracture toughness are 560±32MPa and 32.2±1.5MPa·m 1 / 2 After oxidizing for 50 hours at 1400℃ in a water-oxygen environment of 50vol.%H2O+50vol.%O2, the weight loss rate is only 0.21%, and the corresponding strength retention rate is 85%.
[0114] Embodiment 3
[0115] Step 1. Preparation of porous SiC f / SiC composite materials:
[0116] The CVI process was used to deposit a BN interface phase with a thickness of 180 nm on the woven two-dimensional SiC fiber preform, and then the CVI process was used to deposit the SiC matrix to a semi-densified state to obtain a porous SiC with an open porosity controlled at 30%. f / SiC composite materials;
[0117] Step 2. Preparation of (4RE 0.25 )2Si2O7 particles:
[0118] Four kinds of RE2O3 and SiO2 were mixed in equal molar ratios and sintered at 1550℃ to obtain (4RE 0.25 )2Si2O7, (4RE 0.25 )2Si2O7 was crushed and then milled in a planetary ball mill with ethanol as the milling medium and agate milling beads for 10 hours, and then dried to obtain ceramic particles with a particle size of 3 μm; the four RE2O3 are Y2O3, Tm2O3, Yb2O3 and Lu2O3;
[0119] Step 3. Preparation of (4RE 0.25 )2Si2O7 slurry:
[0120] Sodium carboxymethyl cellulose was added to deionized water in three portions, and a magnetic stirrer was used to quickly disperse the sodium carboxymethyl cellulose in water. Then, the (4RE prepared in step 2 was added. 0.25 )2Si2O7 ceramic particles are ball-milled to obtain (4RE 0.25 )2Si2O7 water-based slurry. (4RE 0.25 )2Si2O7 has a mass fraction of 15wt.%, a mass fraction of sodium carboxymethyl cellulose of 3wt.%, a ball milling time of 24h, and a ball milling speed of 280r / min;
[0121] Step 4.(4RE 0.25 )2Si2O7 slurry impregnation:
[0122] Vacuum impregnation: The porous SiC obtained in step 1 f The SiC composite material was placed in a glass drying dish and vacuumed until the pressure inside the glass dish was lower than -0.09 MPa. After maintaining for 0.5 h, the SiC f The / SiC composite material is immersed in the slurry obtained in step 3 and vacuum is continued for 0.5h;
[0123] Pressure impregnation: Porous SiC f The SiC / SiC composite material and the slurry were placed in a closed container and pressurized to 0.8 MPa, kept for 1 hour, then taken out and dried in an oven at 100°C for 5 hours;
[0124] Repeat this step 3 times until you get (4RE 0.25 )Porous SiC with 2.6 vol.% Si2O7 content f / SiC CVI -(4RE 0.25 )2Si2O7 composite materials;
[0125] Step 5. Preparation of rare earth mono / disilicate mixed matrix layer:
[0126] The porous composite material obtained in step 4 is immersed in the organic precursor (PCS) solution of SiC ceramics. After cross-linking, curing and cracking, PCS and part of the composite material (4RE 0.25 )2Si2O7 reacts to generate (4RE 0.25 )2SiO5, forming a 2.4 vol.% RE-Si-O layer in the porous composite material.
[0127] Step 6. Preparation of PIP SiC substrate layer:
[0128] The SiC matrix was prepared in the porous composite material obtained in step 5 by using the PIP process. The PIP process was repeated 5 times until the density of the composite material reached 2.60 g / cm 3 .
[0129] Step 7. Preparation of (4RE 0.25 )2Si2O7 matrix layer:
[0130] The porous composite material obtained in step 6 was immersed in the slurry obtained in step 3, and step 4 was repeated until 3.4 vol.% (4RE 0.25 )2Si2O7 matrix layer, making the composite material density reach 2.78g / cm 3 ;
[0131] Step 8. Preparation of CVI SiC substrate layer:
[0132] Using the CVI process, a SiC matrix with a thickness of 39.2 μm was prepared in the composite material obtained in step 7, and finally a SiC matrix containing a multilayer matrix was obtained. f / SiC-(4RE 0.25 )2Si2O7-(4RE 0.25 )2SiO5 composite materials.
[0133] Compared with Example 2, the volume fraction of the PIP SiC layer is changed in this example. The matrix of the prepared modified composite material is, from the inside to the outside, a CVI SiC layer with a volume fraction of 25 vol.%, a RE-Si-O layer with a volume fraction of 2.4 vol.%, a PIP SiC layer with a volume fraction of 16.7 vol.%, a (4RE0.25)2Si2O7 layer with a volume fraction of 3.4 vol.%, and a CVI SiC layer with a volume fraction of 1.93 vol.%, and the density is 2.84 g / cm3 and the open porosity is 4%.
[0134] The SiC prepared in this example f / SiC-(4RE 0.25 )2Si2O7-(4RE 0.25 )2SiO5 composite material X-ray diffraction pattern as shown in the attached Figure 4 As shown, it can be seen that the success will (4RE 0.25 )2Si2O7 and (4RE 0.25 )2SiO5 anti-water and oxygen phase is introduced into SiC f / SiC composite materials. SiC f / SiC-(4RE 0.25 )2Si2O7-(4RE 0.25 The force-displacement curve of the 2SiO5 composite material is shown in the attached figure. Figure 5As shown, the material exhibits pseudo-plastic deformation characteristics. The flexural strength and fracture toughness of the composite material are 670±26MPa and 34.8±1.8MPa·m 1 / 2 After oxidation for 50 hours at 1400℃ and in a water-oxygen environment of 50vol.% H2O+50vol.% O2, the weight loss rate was only 0.16%, and the corresponding strength retention rate was 90%.
[0135] Embodiment 4
[0136] Step 1. Preparation of porous SiC f / SiC composite materials:
[0137] The CVI process was used to deposit a BN interface phase with a thickness of 180 nm on the woven two-dimensional SiC fiber preform, and then the CVI process was used to deposit the SiC matrix to a semi-densified state to obtain a porous SiC with an open porosity controlled at 30%. f / SiC composite materials;
[0138] Step 2. Preparation of (4RE 0.25 )2Si2O7 particles:
[0139] Four kinds of RE2O3 and SiO2 were mixed in equal molar ratios and sintered at 1550℃ to obtain (4RE 0.25 )2Si2O7, (4RE 0.25 )2Si2O7 was crushed and then milled in a planetary ball mill with ethanol as the milling medium and agate milling beads for 10 hours, and then dried to obtain ceramic particles with a particle size of 3 μm; the four RE2O3 are Y2O3, Tm2O3, Yb2O3 and Lu2O3;
[0140] Step 3. Preparation of (4RE 0.25 )2Si2O7 slurry:
[0141] Sodium carboxymethyl cellulose was added to deionized water in three portions, and a magnetic stirrer was used to quickly disperse the sodium carboxymethyl cellulose in water. Then, the (4RE prepared in step 2 was added. 0.25 )2Si2O7 ceramic particles are ball-milled to obtain (4RE 0.25 )2Si2O7 water-based slurry. (4RE 0.25 )2Si2O7 has a mass fraction of 15wt.%, a mass fraction of sodium carboxymethyl cellulose of 3wt.%, a ball milling time of 24h, and a ball milling speed of 280r / min;
[0142] Step 4.(4RE 0.25 )2Si2O7 slurry impregnation:
[0143] Vacuum impregnation: The porous SiC obtained in step 1f The SiC composite material was placed in a glass drying dish and vacuumed until the pressure inside the glass dish was lower than -0.09 MPa. After maintaining for 0.5 h, the SiC f The / SiC composite material is immersed in the slurry obtained in step 3 and vacuum is continued for 0.5h;
[0144] Pressure impregnation: Porous SiC f The SiC / SiC composite material and the slurry were placed in a closed container and pressurized to 0.8 MPa, kept for 1 hour, then taken out and dried in an oven at 100°C for 5 hours;
[0145] Repeat this step 3 times until you get (4RE 0.25 )Porous SiC with 2.6 vol.% Si2O7 content f / SiC CVI -(4RE 0.25 )2Si2O7 composite materials;
[0146] Step 5. Preparation of rare earth mono / disilicate mixed matrix layer:
[0147] The porous composite material obtained in step 4 is immersed in the organic precursor (PCS) solution of SiC ceramics. After cross-linking, curing and cracking, PCS and part of the composite material (4RE 0.25 )2Si2O7 reacts to generate (4RE 0.25 )2SiO5, forming a 2.4 vol.% RE-Si-O layer in the porous composite material.
[0148] Step 6. Preparation of PIP SiC substrate layer:
[0149] The SiC matrix was prepared in the porous composite material obtained in step 5 by using the PIP process. The PIP process was repeated 8 times until the density of the composite material reached 2.65 g / cm 3 .
[0150] Step 7. Preparation of (4RE 0.25 )2Si2O7 matrix layer:
[0151] The porous composite material obtained in step 6 was immersed in the slurry obtained in step 3, and step 4 was repeated until 3.4 vol.% (4RE 0.25 )2Si2O7 matrix layer, making the composite material density reach 2.83g / cm 3 ;
[0152] Step 8. Preparation of CVI SiC substrate layer:
[0153] Using the CVI process, a SiC matrix with a thickness of 43.6 μm was prepared in the composite material obtained in step 7, and finally a SiC matrix containing a multilayer matrix was obtained. f / SiC-(4RE 0.25 )2Si2O7-(4RE 0.25 )2SiO5 composite materials.
[0154] Compared with Example 2, the volume fraction of the PIP SiC layer is changed in this embodiment. The matrix of the prepared modified composite material is composed of a CVI SiC layer with a volume fraction of 25 vol.%, a RE-Si-O layer with a volume fraction of 2.4 vol.%, a PIP SiC layer with a volume fraction of 18.3 vol.%, and a (4RE 0.25 )2Si2O7 layer, 2.15vol.% CVI SiC layer, with a density of 2.90g / cm 3 , the open porosity is 2%.
[0155] The SiC prepared in this example f / SiC-(4RE 0.25 )2Si2O7-(4RE 0.25 )2SiO5 matrix distribution characteristics of composite materials such as Figure 6 As shown in the SEM morphology photo, the matrix distribution of the multilayer structure can be seen. The flexural strength and fracture toughness of the composite material are 700±34MPa and 37.8±1.0MPa·m 1 / 2 The composite material lost only 0.11% of its weight after being oxidized for 50 hours in a water-oxygen environment at 1400°C and 50 vol.% H2O+50 vol.% O2. The force-displacement curves before and after water-oxygen corrosion are shown in the figure below. Figure 7 As shown, it can be seen that the composite materials exhibit pseudo-plastic characteristics before and after corrosion. The flexural strength of the composite materials after water-oxygen corrosion is 651 MPa, and the corresponding strength retention rate is 93%.
[0156] Comparative Example
[0157] Step 1. A BN interface with a thickness of 180 nm is deposited on the woven two-dimensional SiC fiber preform by using the CVI process, and then a SiC matrix is deposited to a semi-densified state by using the CVI process to obtain a porous SiC with an open porosity of 30%. f / SiC composite materials;
[0158] Step 2. Prepare the porous SiC fThe / SiC composite material was impregnated in a polycarbosilane solution prepared by mixing polycarbosilane and xylene in a mass ratio of 1:3. After the impregnation, the composite material was placed in a cracking furnace. Under an argon atmosphere, the composite material was kept at 220°C for 1 hour and at 1300°C for 1 hour to prepare a PIP SiC matrix. This step was repeated 5 times to obtain a density of 2.25 g / cm 3 SiC f / SiC composite materials;
[0159] Step 3. Prepare the product in step 2 with a density of 2.25 g / cm 3 SiC f The / SiC composite material was impregnated in a polycarbosilane solution prepared by mixing polycarbosilane and xylene in a mass ratio of 1:1. After the impregnation, the composite material was placed in a cracking furnace. Under an argon atmosphere, the composite material was kept at 220°C for 1 hour and at 1300°C for 1 hour to prepare a PIP SiC matrix. This step was repeated 9 times to obtain a density of 2.61 g / cm 3 , open porosity of 9.6% SiC f / SiC composite materials, the flexural strength and fracture toughness are 630±31MPa and 30.4±1.1MPa·m 1 / 2 After oxidation at 1400℃, 50vol.%H2O+50vol.%O2 for 50h, the weight loss rate is 2%, and the corresponding strength retention rate is 65%.
[0160] The above embodiments are only a part of the embodiments of the present invention. Based on the embodiments of the present invention, various improved and changed embodiments made by those skilled in the art without making creative work and without departing from the method provided by the present invention all belong to the protection scope of the present invention.
Claims
1. A SiC containing multilayer matrix resistant to water and oxygen corrosion f / SiC composite material, characterized by: Composite material is SiC f / SiC-(4RE 0.25 )2Si2O7-(4R 0.25 )2SiO5; the multilayer substrate is CVI SiC layer, RE-Si-O layer, PIP SiC layer, (4RE 0.25 )2Si2O7 layer and CVI SiC layer.
2. The SiC containing multilayer matrix resistant to water and oxygen corrosion according to claim f / SiC composite material, characterized by: The volume fractions of the moduli of each layer are: 21.6-32 vol.% CVI SiC layer, 1.7-2.6 vol.% RE-Si-O layer, 13.2-18.6 vol.% PIP SiC layer, 2.3-3.5 vol.% (4RE 0.25 )2Si2O7 layer and 1.2~3.9vol.% CVI SiC layer.
3. A SiC containing multilayer matrix resistant to water and oxygen corrosion according to claim 1 or 2 f / SiC composite material, characterized in that Here are the steps: Step 1: Preparation of porous SiC f / SiC composite material: The BN interface phase with a thickness of 150-200 nm is deposited on the two-dimensional SiC fiber preform by the CVI process, and then the SiC matrix is deposited to a semi-densified state by the CVI process to obtain a porous SiC f / SiC composite material; the porous SiC f The open porosity of the SiC composite material is controlled to be 20% to 40%; Step 2, (4RE 0.25 )2Si2O7 water-based slurry impregnation: Vacuum impregnation: Porous SiC f The SiC composite material was placed in a glass drying dish and vacuumed to a pressure range of -0.1 to -0.09 MPa. After maintaining for 0.5 to 1 h, the SiC f / SiC composite immersion (4RE 0.25 )2Si2O7 water-based slurry, continue to vacuum for 0.5 to 1h; Pressure impregnation: Porous SiC f The / SiC composite material and the slurry are placed in a closed container and pressurized to 0.7-0.9 MPa, maintained for 0.5-1 hour, then taken out and dried; Get (4RE 0.25 )2Porous SiC with Si2O7 content of 1.9 to 2.9 vol.% f / SiC CVI -(4RE 0.25 )2Si2O7 composite materials; Step 3: Preparation of rare earth mono / disilicate mixed matrix layer: The porous composite material obtained in step 2 is immersed in the organic precursor PCS solution of SiC ceramics. After cross-linking, curing and cracking, PCS and part of the composite material (4RE 0.25 )2Si2O7 reacts to form X2 phase high entropy rare earth monosilicate, referred to as ((4RE 0.25 )2SiO5), forming a 1.7-2.6 vol.% rare earth mono / disilicate mixed matrix layer (abbreviated as RE-Si-O) in the porous composite material; Step 4: Prepare PIP SiC matrix layer: Prepare SiC matrix in the porous composite material obtained in step 3 by PIP process, and repeat the PIP process several times until the density of the composite material reaches 2.40-2.68 g / cm 3 ; Step 5: Preparation (4RE 0.25 )2Si2O7 matrix layer: The porous composite material obtained in step 4 is immersed in (4RE 0.25 )2Si2O7 water-based slurry, repeat step 2 until 2.3-3.5 vol.% (4RE 0.25 )2Si2O7 matrix layer, making the composite material density reach 2.53~2.87g / cm 3 ; Step 6: Prepare CVI SiC matrix layer: Prepare SiC matrix in the composite material obtained in step 5 by CVI process to obtain SiC containing multilayer matrix. f / SiC CVI -(RE-Si-O)-SiC PIP -(4RE 0.25 )2Si2O7-SiC CVI Composite material, referred to as SiC f / SiC-(4RE 0.25 )2Si2O7-(4RE 0.25 )2SiO5 composite materials; The SiC substrate has a thickness of 30 to 50 μm.
4. The method according to claim 3, characterized in that: The (4RE 0.25 The preparation of 4RE2Si2O7 slurry is as follows:
1. Four RE2O3 and SiO2 are mixed evenly in equal molar ratios and then sintered at 1300-1700°C to obtain β-phase high entropy rare earth double silicate ceramics (abbreviated as (4RE 0.25 )2Si2O7), (4RE 0.25 )2Si2O7 was crushed and milled in a planetary ball mill with ethanol as the ball milling medium and agate ball milling beads for 5 to 15 hours, and then dried to obtain ceramic particles with a particle size of 1 to 10 μm; sodium carboxymethyl cellulose was added to deionized water in 3 to 6 portions, and a magnetic stirrer was used to quickly disperse the sodium carboxymethyl cellulose in the water, and then (4RE 0.25 )2Si2O7 ceramic particles are ball-milled to obtain (4RE 0.25 )2Si2O7 water-based slurry; (4RE 0.25 )The mass fraction of 2Si2O7 is 10-30wt.%, the mass fraction of sodium carboxymethyl cellulose is 3-5wt.%, the ball milling time is 8-24h, and the ball milling speed is 100-380r / min.
5. The method according to claim 4, characterized in that: The RE2O3 is selected from any four of Sc2O3, Y2O3, Tb2O3, Ho2O3, Er2O3, Tm2O3, Dy2O3, Gd2O3, Yb2O3, and Lu2O3.
6. The method according to claim 3, characterized in that: The drying temperature in the pressure impregnation of step 2 is 80° C. to 150° C., and the drying time is 4 to 8 hours.
7. The method according to claim 3, characterized in that: In step 3, the PCS solution of the organic precursor of SiC ceramic is prepared by mixing polycarbosilane and xylene in a mass ratio of 1:1 to 1:
20.
8. The method according to claim 3, characterized in that: The cross-linking, curing and cracking process in step 3 is: in an argon atmosphere, the composite material is kept at 200-240° C. for 1-2 hours and at 1300-1400° C. for 2-3 hours.
9. The method according to claim 3, characterized in that: The PIP process in step 4 is: in an argon atmosphere, the composite material is kept at 220° C. for 1 to 2 hours, and at 1000 to 1300° C. for 1 to 2 hours.
10. A SiC containing multi-layer matrix resistant to water and oxygen corrosion according to claim 1 or 2 f / Application of SiC composite materials, characterized by: The density of the composite material is 2.58-2.98 g / cm 3 , the open porosity is 2% to 8%. After being corroded in a water-oxygen environment at 1100 to 1400°C and 50 vol.% H2O + 50 vol.% O2 for 50 to 200 hours, the weight loss rate of the modified composite material is only 0.11 to 0.5%, and the strength retention rate exceeds 93%. SiC f The water-oxygen corrosion resistance of SiC composite materials is greatly improved, making it an ideal material for aircraft engines in high temperature and water-oxygen corrosion coupling environments, which helps to improve the working efficiency of the engine.
Citation Information
Patent Citations
Method of depositing abradable coatings under polymer gels
CN105814144A
High-temperature-resistant ultrahigh-porosity high-entropy rare earth silicate and preparation method thereof
CN117285338A
High-entropy ceramic-based composite material and preparation method thereof
CN117567158A
Multiphase oxide ceramic modified ceramic-based composite material and preparation method thereof
CN117923928A
Protective coating systems for gas turbine engine applications and methods for fabricating the same
EP4124613A1